1997
DOI: 10.1023/a:1018821200354
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: It is unknown whether bacteriolysis due to luminal complement activation contributes to local defense mechanisms against small intestinal bacterial overgrowth, particularly with gram-negative bacteria. This study addressed this issue. Thirty adult subjects were investigated with culture of luminal secretions adherent to proximal small intestinal mucosa. Luminal and plasma concentrations of C3 and C3d and C3d/C3 ratios were determined. Activated terminal complement complex was sought in surface epithelium to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In another report that measured complement in lumen samples, higher C3 and C4 levels were found in jejunal secretions from Crohn’s disease patients compared to healthy participants ( 58 ). Complement proteins were also detected in lumen samples collected from the small intestine of patients experiencing bacterial overgrowth ( 59 ). Noteworthy, and at odds with complement in the lumen, these authors failed to find MAC proteins, suggesting the MAC is not present (active) in the lumen.…”
Section: Complement and The Intestinementioning
confidence: 99%
“…In another report that measured complement in lumen samples, higher C3 and C4 levels were found in jejunal secretions from Crohn’s disease patients compared to healthy participants ( 58 ). Complement proteins were also detected in lumen samples collected from the small intestine of patients experiencing bacterial overgrowth ( 59 ). Noteworthy, and at odds with complement in the lumen, these authors failed to find MAC proteins, suggesting the MAC is not present (active) in the lumen.…”
Section: Complement and The Intestinementioning
confidence: 99%
“…Early serum depletion studies have suggested that vibriocidal titers are primarily derived from LPS O-antigen-specific IgM and, to a lesser extent, IgG1 and IgG3 antibodies (7,23). Despite this, complement-mediated protection is unlikely to be a critical component of mucosal immunity to a noninvasive bacterial pathogen given the small amount of complement in the intestinal tract (24,25). Moreover, vibriocidal titers decline to baseline levels before protective immunity wanes (26).…”
mentioning
confidence: 99%